2019
DOI: 10.1055/s-0039-1696700
|View full text |Cite
|
Sign up to set email alerts
|

Audiological Abnormalities in Vitiligo Patients: A Hospital-Based Cross-Sectional Study

Abstract: Introduction There are some discrepancies in the literature about the influence of vitiligo on auditory functions. According to some authors, vitiligo influences hearing, whereas others question such influence. Therefore, we conducted a study to evaluate audiological functions in vitiligo patients. Objectives To determine the effect of vitiligo on auditory functions. Methods A hospital-based observational study was done from January 2017 to July 2017. Clinically diagnosed cases of vitiligo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A greater exposure to audiological disturbances has been observed in older patients. In addition, vitiligo patients should avoid noise and ototoxic drugs [15]. Sheng-Hsiang et al reached similar conclusions -regular audiologic assessment is indicated in patients with vitiligo in order to detect hearing disorders earlier.…”
Section: Scientific Research Resultsmentioning
confidence: 82%
“…A greater exposure to audiological disturbances has been observed in older patients. In addition, vitiligo patients should avoid noise and ototoxic drugs [15]. Sheng-Hsiang et al reached similar conclusions -regular audiologic assessment is indicated in patients with vitiligo in order to detect hearing disorders earlier.…”
Section: Scientific Research Resultsmentioning
confidence: 82%
“…41,42 Also, melanocytes regulate potassium channels involved in the endocochlear electrical potential that is important in signal transmission of auditory function. [43][44][45] The amounts of melanin are most abundant at the cochlea base which is in charge of high-frequency hearing only. 46,47 Anti-melanocyte antibodies presenting in vitiligo can attack the inner ear melanocytes, resulting in decreased amounts of melanin and increased susceptibility to highfrequency sensorineural hearing loss, which is compatible with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Melanin mitigates free radical damage from ototoxic environment via acting as the Ca 2+ chelator in cationic exchange, modulates the calcium homeostasis, and consequently, regulates redox balance and prevents DNA damage in cells 41,42 . Also, melanocytes regulate potassium channels involved in the endocochlear electrical potential that is important in signal transmission of auditory function 43–45 . The amounts of melanin are most abundant at the cochlea base which is in charge of high‐frequency hearing only 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, although the mean age of the vitiligo patients was 40 years, there was no significant difference between the groups in hearing loss measured by the C-PTA test. However, Prabha et al16 reported that elderly patients with vitiligo had a higher risk of audiometric abnormalities. There are also studies reporting that vitiligo was associated with hearing loss in the C-PTA test 5,17.…”
mentioning
confidence: 99%